Disordering Behavior Pattern in Autistic Students - Bebi Sindi Putra; Marlina Marlina (Edumaspul: Jurnal Pendidikan, 2022)
Abstract Autistic students experience barriers to behavior, communication, and social interaction. Based on a preliminary study, it was found that autistic students did not respond to people around them, were often alone, and rarely played. The purpose of this study was to describe the pattern of disruptive behavior in autistic students. Subject selection is done by means of identification of children with special needs and assessment of disruptive behavior. The research design is a qualitative case study with a descriptive method. Data were collected by observation and interviews. Observations were used to observe verbally and physically disruptive behavior the teacher's role in overcoming disruptive behavior, as well as the impact of disruptive behavior on autistic students. Interviews were used to get answers orally to classmates and class teachers, principals, parents, neighbors. The data were analyzed using componential analysis which analyzed more specifically the focus of the research. The results of the study showed that autistic students' verbally disruptive forms of behavior such as making fun of and calling with bad names. The forms of behavior that physically interfere with autistic students are attacking, pulling the headscarf, pulling hair, and pulling friends' hands. The teacher plays an authoritative role in overcoming the disruptive behavior raised by autistic students. The impact of disruptive behavior on the person being bullied is feeling uncomfortable and angry. The impact of behavior on autistic students themselves is being attacked and ostracized. It is recommended for teachers to provide assertiveness, collaborate with behavioral therapists and competent experts. Keywords: Disturbing behavior; the role of the teacher; impact; autistic students.